Production of Mannooligosaccharides from Açaí Seed by Immobilized β-Mannanase - Murillo-Franco, Sarha Lucia [UNESP]; Galvis-Nieto, Juan David; Orrego, Carlos E. (MDPI, 2024)
In this work, an enzyme cocktail with β-mannanase as the main activity was immobilized on epoxy resin foams filled with fibers from annatto capsules. The catalytic system was characterized by SEM, FTIR, and a mechanical crush resistance test. The behavior of the pH and temperature for the hydrolysis of the locust bean gum were also studied. With the same substrate and with respect to the free enzyme, the immobilized enzyme showed an activity retention of 79.61%. Its operational stability in ten reuse cycles did not show any statistically significant loss of activity. This catalytic system was used to study the preferential release of MOS of two to five degrees of polymerization from mannan present in dried and ground açaí seeds, which were not subjected to any other pretreatment. Using an experimental response surface design, the predicted quadratic models for the M2–M5 MOS content were obtained and they fit well with the experimental data, predicting a production range between 0.435 and 20 g/L of MOS (M2–M5). In addition, the production reached about 12 g/L under the optimized conditions. These results indicate that the used foamed epoxy resin supports and immobilization methodology are suitable for catalyzing the hydrolysis of mannan from açaí seeds.
Keywords: açai seeds; enzymatic hydrolysis; immobilized systems; mannooligosaccharides production; waste valorization